Rethrethinking Islamic Theology Mengagas Teologi Sosial dalam konteks Pluralisme dan Multikulturalisme (Perspektif Pemikiran Teologi Fethullah Gulen) - Muhammad Said (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
This article elaborate about the neccesity of renewal Islamic theology in the context of pluralism and multiculturalism. One of contemporary Muslim schoolars, Fethullah Gulen, could be considered among the most influential Muslim theologians in the context of modern world. His works focus on redef ining the nature of Islamic discourse in the contemporary world by doing interreligious and intercultural dialogue. Today, we need to shift our paradigm from classical kalam which dogmatic, abstract, and exclusive, to be more practical theology, based on contemporary needs of human life, by presenting as what is called “social theology”. It’s important to note that Gulen’s theological discourse distinguished for his support of democracy, humanisme, openness to globalization, progressiveness in integrating tradition with modernity, and to make sense of pluralistic-piety.[Artikel ini menjelaskan tentang kepentingan dibalik agenda pembaharuan teologi Islam dalam konteks pluralisme dan multikulturalisme. Salah satu pemikir Muslim kontemporer, Fethullah Gulen, dianggap sebagai salah satu teolog Muslim paling berpengaruh dalam konteks dunia modern saat ini. Karya-karyanya fokus pada upaya pendefinisian ulang tentang wacana- wacana Islam di dunia kontemporer dengan melakukan dialog antaragama dan antarbudaya. Saat ini, kita perlu merubah paradigma kita dari kalam klasik yang dogmatis, abstrak, dan eksklusif, menjadi teologi lebih praktis, berdasarkan kebutuhan kontemporer, yakni dengan menghadirkan apa yang disebut dengan “teologi sosial”. penting dicatat bahwa wacana teologis Gulen ini dibedakan atas dukungan demokrasi, humanisme, keterbukaan terhadap globalisasi, progresif dalam mengintegrasikan tradisi dengan modernitas, serta untuk memahami kesalehan pluralistik.]